2011
DOI: 10.1210/jc.2011-1231
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 135 Regulates HOXA10 Expression in Endometriosis

Abstract: HOXA10 was aberrantly regulated in the endometrium of women with endometriosis by both miR135a and miR135b. Increased microRNA expression likely suppresses genes required for implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 29 publications
5
89
1
2
Order By: Relevance
“…For example, down-regulation of miR-9* has been demonstrated in the endometria (33) as well as serum samples (16) of women with endometriosis, but most of the reported endometriosisassociated dysregulated endometrial miRNAs have not been shown to be altered in plasma. Interestingly, miR-135a that was overexpressed in the endometrium of endometriosis patients (35) showed significantly lower levels in sera of patients with endometriosis compared with control subjects (18). We previously demonstrated that miR-200a, miR-200b, and miR-141 are not differentially expressed in the endometrium of women with and without endometriosis (22), so endometrium is likely not the tissue of origin for the miR-200 plasma alterations in endometriosis.…”
Section: Discussionmentioning
confidence: 94%
“…For example, down-regulation of miR-9* has been demonstrated in the endometria (33) as well as serum samples (16) of women with endometriosis, but most of the reported endometriosisassociated dysregulated endometrial miRNAs have not been shown to be altered in plasma. Interestingly, miR-135a that was overexpressed in the endometrium of endometriosis patients (35) showed significantly lower levels in sera of patients with endometriosis compared with control subjects (18). We previously demonstrated that miR-200a, miR-200b, and miR-141 are not differentially expressed in the endometrium of women with and without endometriosis (22), so endometrium is likely not the tissue of origin for the miR-200 plasma alterations in endometriosis.…”
Section: Discussionmentioning
confidence: 94%
“…Evidence suggested that the expression of VEGFA was highly regulated in a temporal and spatial manner at the early stage of implantation [46]. HOXA10, a homeobox-containing transcription factor, expressed cyclically during the menstrual cycle in the endometrium under the influence of steroid hormone, and had the highest expression level during WOI [47,48]. OPN played an important role in endometrial receptivity due to its consistent up-regulation during the WOI [49].…”
Section: Mir-181a Might Participate In the Formation Of Endometrial Rmentioning
confidence: 99%
“…We confirmed with miR-specific quantitative PCR that miR-30b, -30d, -31, and -203 were significantly overexpressed and miR-503 and -145 were significantly under-expressed in endometrial tissue obtained in the mid-secretory phase as compared to the proliferative phase (Table2). Since miR135a and -135b have been implicated as important regulators of HOX genes during implantation [35,36], we also examined their expression but found no difference between CD 7-10 and 20-24 (Table 2).…”
Section: Differential Endometrial Mirna Expression In the Window Of Imentioning
confidence: 99%